2017
DOI: 10.3389/fnbeh.2017.00211
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity Analysis of the Brain Network in Drivers during Actual Driving Using Near-Infrared Spectroscopy

Abstract: Driving a vehicle is a complex activity that requires high-level brain functions. This study aimed to assess the change in effective connectivity (EC) between the prefrontal cortex (PFC), motor-related areas (MA) and vision-related areas (VA) in the brain network among the resting, simple-driving and car-following states. Twelve young male right-handed adults were recruited to participate in an actual driving experiment. The brain delta [HbO2] signals were continuously recorded using functional near infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 67 publications
(74 reference statements)
0
29
0
Order By: Relevance
“…Therefore, fNIRS has many advantages over other neuroimaging modalities; its application has great potential in studying the functional imaging of the brain [51], perception and cognition [52], behavioral and cognitive neurodevelopment [53,54], somatosensory and bundled optode configuration [55,56], stroke and brain injury [57,58], and brain-computer interfaces [59,60]. Moreover, various studies have used fNIRS to investigate functional connectivity in different brain regions [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fNIRS has many advantages over other neuroimaging modalities; its application has great potential in studying the functional imaging of the brain [51], perception and cognition [52], behavioral and cognitive neurodevelopment [53,54], somatosensory and bundled optode configuration [55,56], stroke and brain injury [57,58], and brain-computer interfaces [59,60]. Moreover, various studies have used fNIRS to investigate functional connectivity in different brain regions [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the activation in the PFC was higher in the two-dimensional task than that in the one-dimensional task, revealing that the subjects increased the recruitment of the PFC in response to the additional visual input within two-dimensional MCI, which could increase cognitive workload and consequently caused the higher neural activity in the PFC [51]. Liu et al pointed out that the hemodynamic activation in the PFC showed an increasing tendency with the increase of cognitive workload [52]. Basso et al testified that the activation in the PFC was related to the difficulty level of the task, since the harder task could incur more cognitive workload and then require higher activation in the PFC [53].…”
Section: Discussionmentioning
confidence: 54%
“… 79 Effective connectivity has been applied in several fNIRS studies. 80 – 82 In addition, although multiple popular group-level statistical models are provided, individual-level statistical tests are not supported in the current version of NIRS-KIT. We plan to incorporate these functionalities to future versions of NIRS-KIT.…”
Section: Discussionmentioning
confidence: 99%